Evaluation of TgH(CX3CR1-EGFP) mice implanted with mCherry-GL261 cells as an in vivo model for morphometrical analysis of glioma-microglia interaction. Issue 1 (December 2016) - Resende, Fernando; Bai, Xianshu; Del Bel, Elaine; Kirchhoff, Frank; Scheller, Anja; Titze-de-Almeida, Ricardo
Abstract Background Glioblastoma multiforme is the most aggressive brain tumor. Microglia are prominent cells within glioma tissue and play important roles in tumor biology. This work presents an animal model designed for the study of microglial cell morphology in situ during gliomagenesis. It also allows a quantitative morphometrical analysis of microglial cells during their activation by glioma cells. Methods The animal model associates the following cell types: 1- mCherry red fluorescent GL261 glioma cells and; 2- EGFP fluorescent microglia, present in the TgH(CX3CR1-EGFP) mouse line. First, mCherry-GL261 glioma cells were implanted in the brain cortex of TgH(CX3CR1-EGFP) mice. Epifluorescence − and confocal laser-scanning microscopy were employed for analysis of fixed tissue sections, whereas two-photon laser-scanning microscopy (2P-LSM) was used to track tumor cells and microglia in the brain of living animals. Results Implanted mCherry-GL261 cells successfully developed brain tumors. They mimic the aggressive behavior found in human disease, with a rapid increase in size and the presence of secondary tumors apart from the injection site. As tumor grows, mCherry-GL261 cells progressively lost their original shape, adopting a heterogeneous and diffuse morphology at 14–18 d. Soma size increased from 10–52 μm. At this point, we focused on the kinetics of microglial access to glioma tissues. 2P-LSM revealed an intense microgliosis in brain areas already shortly after tumor implantation, i.e. at 30 min. By confocal microscopy, we found clusters of microglial cells around the tumor mass in the first 3 days. Then cells infiltrated the tumor area, where they remained during all the time points studied, from 6–18 days. Microglia in contact with glioma cells also present changes in cell morphology, from a ramified to an amoeboid shape. Cell bodies enlarged from 366 ± 0.0 μm2, in quiescent microglia, to 1310 ± 146.0 μm2, and the cell processes became shortened. Conclusions The GL261/CX3CR1 mouse model reported here is a valuable tool for imaging of microglial cells during glioma growth, either in fixed tissue sections or living animals. Remarkable advantages are the use of immunocompetent animals and the simplified imaging method without the need of immunohistochemical procedures.